2020
DOI: 10.1088/1755-1315/592/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Disaster learning through a map-based mobile application: an evaluation of its readability and user satisfaction

Abstract: Mobile technologies have become a key potential learning tool for the public in this digital era, particularly for young people. The Indonesian government, through its National Disaster Management Agency, has developed and launched a mobile application called InaRisk Personal to help citizens become more aware of disasters. This paper aims to assess whether this map-based application is effective and efficient as a disaster learning tool for senior high school students by evaluating its readability (efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This application was developed jointly by the government and other parties who had experience in disaster education in Indonesia. This application was developed by the National Disaster Management Agency with support from the Ministry of Energy and Mineral Resources, the Ministry of Public Works and Public Housing, and the Meteorology, Climatology, and Geophysics Agency as well as other institutions, especially in providing data (Sari, Komalasari, & Kanegae, 2020). InaRISK Personal will be developed continuously and evolve to meet the needs of updating data, information, and methodologies that provide benefits to the community.…”
Section: Resultsmentioning
confidence: 99%
“…This application was developed jointly by the government and other parties who had experience in disaster education in Indonesia. This application was developed by the National Disaster Management Agency with support from the Ministry of Energy and Mineral Resources, the Ministry of Public Works and Public Housing, and the Meteorology, Climatology, and Geophysics Agency as well as other institutions, especially in providing data (Sari, Komalasari, & Kanegae, 2020). InaRISK Personal will be developed continuously and evolve to meet the needs of updating data, information, and methodologies that provide benefits to the community.…”
Section: Resultsmentioning
confidence: 99%
“…Through its National Disaster Management Agency, the Indonesian government has developed and launched a mobile application called InaRisk Personal to help citizens become more aware of disasters. Sari et al (2020) assessed whether InaRisk Personal is effective as a disaster learning tool for senior high school students, and collected 361 questionnaires from four high schools. They found that the application on mobile devices has provided higher map readability and user satisfaction compared to printed maps.…”
Section: )mentioning
confidence: 99%
“…The specific mechanisms linking climate change and mental health are still being explored [26]; however, the occurrence of specific climate change-related events (i.e., extreme heat waves, flooding) have been found to increase stress, headaches, psychiatric hospitalizations, post-traumatic stress disorder, and suicide rates -particularly among patients with pre-existing mental health conditions, and among climate refugees who have been displaced [26][27][28][29][30][31][32][33]. In addition to the direct impacts of climate change on mental health, studies have also shown indirect impacts of climaterelated events such as heatwaves on human behaviour, including increased aggression and criminal activity [34][35][36], as well as low mood and impaired cognitive functioning resulting from heat stress [34,37,38]. Overall, adverse mental health impacts are worse among populations experiencing vulnerability, as they often lack control over climate change adaptation and mitigation strategies [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, researchbased digital apps such as 'Siaga Bencana' and the 'Kanazawa and Kochi Disaster Preparedness System' leverage technology to assist individuals in areas prone to natural disasters [36,37]. Moreover, apps like 'InaRisk Personal' use innovative tools such as cartographic visualization to help improve knowledge of environmental hazards among youth [38] Despite these advances, there is limited evidence of mobile apps focusing on food insecurity or mental health in a climate emergency.…”
Section: Introductionmentioning
confidence: 99%